Birth weight and obstetric complications determine age at onset in first episode of psychosis. (June 2015) - Rubio-Abadal, E.; Ochoa, S.; Barajas, A.; Baños, I.; Dolz, M.; Sanchez, B.; Del Cacho, N.; Carlson, J.; Huerta-Ramos, E.; Usall, J.; ,
Abstract: Background: Earlier age at onset of psychosis (AOP) has been associated with poor social adjustment and clinical outcome. Genetic and environmental factors such as obstetric complications, parental history of psychosis, advanced paternal age at time of birth, low birth weight and gestational age, and use of drugs have been described as bringing AOP forward. This study aims to evaluate the relationship between AOP and these factors in a sample of first episode of psychosis (FEP) patients. Methods: Clinical and sociodemographic data, age at FEP, age of parents at birth, parental history of psychosis, drug-use habits of the mother during pregnancy and of the patient before psychotic onset, and Lewis and Murray obstetric complication scale were obtained from 90 patients with FEP. Statistical analysis was performed by means of Pearson correlations, Chi-square tests, Student T-test analyses and a linear regression model using SPSS version 22. Results: Pre-eclampsia, need for incubator at birth, use of forceps, parental history of psychosis, and low birth weight were associated with an earlier AOP. Use of forceps and birth weight are the variables which best predict AOP in FEP. Stimulant drugs, which were mostly used together with cannabis and cocaine, were the only substances associated with an earlier AOP. Conclusions: Our findings are consistent with previous study results and underline the role of the prenatal period in the development of psychosis and the importance of careful monitoring of pregnancy and delivery, especially in cases with familial history. Highlights: We aim to examine how psychosis antecedents and obstetric characteristics affect age at onset of psychosis. New perspective: only first episode of psychosis patients are included. Pre-eclampsia, incubator, forceps, antecedents of psychosis and low birth weight were associated with earlier age at onset. Use of forceps and birth weight best predict age at onset. Prenatal period has an important role in the development of psychosis and schizophrenia.